E-Planning System in the Regional Development Planning Agency of Gorontalo District - Mayanggita, Adelia; Tilome, Apris Ara; Djafar, Franky (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the implementation of the e-Planning system in the Regional Development Planning Agency ancy (Bappeda) of Gorontalo Regency using the Technology-Organization-Environment (TOE) approach. The method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the implementation of the e-Planning system has not been running optimally and still faces various obstacles in three main aspects. From the technological aspect, unstable internet network interference is a dominant obstacle that causes delays and failures in system access. From the organizational aspect, the available SOPs are still general and have not been adapted to the technical needs of each sector, resulting in inconsistencies in task implementation Meanwhile, from the environmental side, the low understanding and technical skills of human resources. as well as unequal training, are challenges in optimizing system use. This study recommends improving network infrastructure, re-drafting more contextual SOPs and ongoing technical training to increase the effectiveness of e-Planning implementation in the Bappeda of Gorontalo Regency.